KEDUDUKAN KETETAPAN MPR DALAM HIERARKI PERATURAN PERUNDANG-UNDANGAN BERDASARKAN UU NOMOR 12 TAHUN 2011 - Masriyani Masriyani (Jurnal LEX SPECIALIS, 2012)
Abstract Law No. 12 Year 2011 on the Establishment Regulation Legislation is the implementation of the implementation of the People's Consultative Assembly Decree as a hierarchy of legislation in Indonesia. In the description of this paper tries to examine two things: first, an analysis of the basic consideration of the inclusion of the PCA provisions in the hierarchy of legislation, both the analysis of the position of the PCA provisions in the legislation system in accordance with Law No. 12 Year 2011. Amendment Act of 1945 has changed the position of the People's Consultative Assembly of the highest state institution into an institution of the country. These changes also have implications on the product law (statutes Consultative Assembly) which is born of laws MPR after the determination is subject to review only (beschiking) and is set to the (internal regulation). And according to Article 2 and 4 Decree of the People's Consultative Assembly of the Republic of Indonesia Number I/MPR/2003 was declared valid. The position of the PCA provisions under Law no. 12 In 2011, placed under the Act Key Note : hierarchy of legislation